Scaling Effects on the Electrochemical Performance of poly(3, 4‐ethylenedioxythiophene (PEDOT), Au, and Pt for Electrocorticography Recording. (8th September 2017) - Ganji, Mehran; Elthakeb, Ahmed T.; Tanaka, Atsunori; Gilja, Vikash; Halgren, Eric; Dayeh, Shadi A.
Abstract: Reduced contact size would permit higher resolution cortical recordings, but the effects of diameter on crucial recording and stimulation properties are poorly understood. Here, the first systematic study of scaling effects on the electrochemical properties of metallic Pt and Au and organic poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) electrodes is presented. PEDOT:PSS exhibits better faradaic charge transfer and capacitive charge coupling than metal electrodes, and these characteristics lead to improved electrochemical performance and reduced noise at smaller electrode diameters. PEDOT:PSS coating reduces the impedances of metallic electrodes by up to 18x for diameters <200 µm, but has no effect for millimeter scale contacts due to the dominance of series resistances. Therefore, the performance gains are especially significant at smaller diameters and lower frequencies essential for recording cognitive and pathological activities. Additionally, the overall reduced noise of the PEDOT:PSS electrodes enables a lower noise floor for recording action potentials. These results permit quantitative optimization of contact material and diameter for different electrocorticography applications. Abstract : Electrode arrays are fabricated using metal (Pt, Au) and organic (poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS)) coatings. Their electrochemical sensing characteristics are studied and quantified as a function of diameter for different frequency bands and at different size regimes. The results can guide the design and operation of ECoG electrode arrays.